Beyond menstrual hygiene: addressing vaginal bleeding throughout the life course in low and middle-income countries. Issue 2 (27th July 2017) - Sommer, Marni; Phillips-Howard, Penelope A; Mahon, Therese; Zients, Sasha; Jones, Meredith; Caruso, Bethany A
Abstract : Girls and women experience numerous types of vaginal bleeding. These include healthy reproductive processes, such as menstruation and bleeding after childbirth, but also bleeding related to health conditions, such as fibroids or cancer. In most societies, the management of menstruation is handled covertly, something girls are often instructed about at menarche. The management of other vaginal bleeding is often similarly discreet, although behaviours are not well documented. In many societies, cultural taboos frequently hinder open discussion around vaginal bleeding, restricting information and early access to healthcare. Additionally, the limited availability of clean, accessible water and sanitation facilities in many low and middle-income countries augments the challenges girls and women face in conducting daily activities while managing vaginal bleeding, including participating in school or work, going to the market or fetching water. This paper aims to highlight the key vaginal bleeding experiences throughout a woman's life course and the intersection of these bleeding experiences with their access to adequate water and sanitation facilities, information and education sources, and supplies. The aim is to address the silence around girls and women's vaginal bleeding and their related social, physical and clinical management needs across the life course; and highlight critical gaps that require attention in research, practice and policy around this neglected topic of health and gender equality.